The Role Of Foreign Investment In Accelerating Economic Growth In Indonesia - Sidebang, Tamaria Br; Vingky Dwi Pratama; Novita Sari Br Kaban; Marshanda Hutagalung (Outline Journal of Economic Studies, 2025)
The role of foreign investment greatly determines the rate of growth of the national economy such as the number of improvements to infrastructure and facilities and infrastructure. Types of normative juridical research. The nature of the research is descriptive. Data collection techniques use primary, secondary and tertiary data. Data analysis uses qualitative analysis. The role of foreign investment makes a real contribution to the economy. technological development, improving infrastructure as well as creating jobs and generating state revenue Obstacles that arise are complicated regulations, difficult land acquisition, uneven public infrastructure, taxes and other non-fiscal incentives do not support investment and inadequate skilled workforce Efforts to attract foreign investment in accelerating national economic growth including infrastructure, skilled workforce, ease of licensing, incentives from the government, legal guarantees and community welfare.